A leucopoietic-arterial axis underlying the link between ambient air pollution and cardiovascular disease in humans. (11th January 2021) - Abohashem, Shady; Osborne, Michael T; Dar, Tawseef; Naddaf, Nicki; Abbasi, Taimur; Ghoneem, Ahmed; Radfar, Azar; Patrich, Tomas; Oberfeld, Blake; Tung, Brian; Fayad, Zahi A; Rajagopalan, Sanjay; et al.
Abstract: Aims : Air pollution [i.e. particulate matter with diameter <2.5 μm (PM2.5 )] is a risk factor for major adverse cardiovascular events (MACE). While PM2.5 promotes leucopoiesis and atherosclerotic inflammation in experimental models, it is unknown whether this occurs in humans. We tested in humans (a) whether PM2.5 associates with higher leucopoietic tissue activity and arterial inflammation (ArtI), (ii) whether these associations persist after accounting for the effects of potential confounders including socioeconomics, traffic noise, and risk factors, and (iii) whether these tissue effects mediate the association between air pollution and MACE. Methods and results : Individuals ( N = 503) without cardiovascular disease (CVD) or active malignancy underwent 18 F-fluorodeoxyglucose positron emission tomography/computed tomography. Major adverse cardiovascular event was adjudicated over 5 years of follow-up. Leucopoietic tissue activity (in bone marrow and spleen) as well as ArtI were measured. Annual PM2.5 levels were assessed at each individual's home address. At baseline, higher PM2.5 associated with increased leucopoietic activity [standardized (95% CI): 0.129 (0.042, 0.215), P = 0.004] as well as ArtI [0.088 (0.006, 0.171), P = 0.036] after adjusting for CVD risk factors. Over a median 4.1 years, 40 individuals experienced MACE. PM2.5 exposure associated with MACE [Cox HR (95% CI): 1.404 (1.135, 1.737), P = 0.002], remaining significant after adjustment for CVD risk factors and other potential confounders. Mediation analysis demonstrated that increased leucopoietic activity and ArtI serially mediate the link between PM2.5 exposure and MACE. Conclusions : Higher air pollution exposure associates with heightened leucopoietic activity and ArtI and independently predicts MACE through a biological pathway that includes higher leucopoietic activity and ArtI in series. Graphical Abstract: